Analisis Pragmatik Tindak Tutur Asertif pada Podcast Close The Door Episode “Ayolah Masa Kalian Ga Tau Tujuannya Apa dan Amannya Indonesia!” - Suci Rahmadani; Alber Alber (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to identify the forms, functions, and the most dominant types of assertive speech acts in digital communication. Using a descriptive qualitative approach with content analysis methods, data were collected through observation and note-taking techniques from the Close The Door podcast episode entitled